Measuring job satisfaction of educational counselors working in secondary schools in Maysan province - Ashraf Saleh Jassim ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2020)
The current research aims                            1.Measuring the level of job satisfaction for educational counselors working in secondary schools in Maysan Governorate 2.Knowing the level of job satisfaction with educational counselors working in secondary schools in Maysan GovernorateTo achieve the goals of the current research, the following procedures were followed:Choose an appropriate sample from the research community.B. The researcher adopted the scale: Job Satisfaction, prepared by (Al-Shehri, Ali